A hot tip: imaging phenomena using in situ multi-stimulus probes at high temperatures. Issue 6 (22nd January 2016) - Nonnenmann, Stephen S.
Abstract : Here we review high temperature, ambient pressure in situ SPM imaging to promote local, temperature-dependent catalytic, electronic, and electrochemical-based studies. Abstract : Accurate high temperature characterization of materials remains a critical challenge to the continued advancement of various important energy, nuclear, electronic, and aerospace applications. Future experimental studies must assist these communities to progress past empiricism and derive deliberate, predictable designs of material classes functioning within active, extreme environments. Successful realization of systems ranging from fuel cells and batteries to electromechanical nanogenerators and turbines requires a dynamic understanding of the excitation, surface-mediated, and charge transfer phenomena which occur at heterophase interfaces ( i.e. vapor–solid, liquid–solid, solid–solid) and impact overall performance. Advancing these frontiers therefore necessitates in situ (operando) characterization methods capable of resolving, both spatially and functionally, the coherence between these complex, collective excitations, and their respective response dynamics, through studies within the operating regime. This review highlights recent developments in scanning probe microscopy in performing in situ imaging at high elevated temperatures. The influence of and evolution from vacuum-based electron and tunneling microscopy are briefly summarized and discussed. The scope includes the use of high temperature imaging to directly observe critical phase transition, electronic, and electrochemical behavior under dynamic temperature settings, thus providing key physical parameters. Finally, both challenges and directions in combined instrumentation are proposed and discussed towards the end.